2014
DOI: 10.1002/ccd.25732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on the prognostic value of left ventricular function in relation to procedural outcomes following percutaneous coronary intervention: Insights from the British cardiovascular intervention society

Abstract: Our analysis suggests that worsening LV function is an important independent predictor of worse 30-day mortality outcomes across all age groups and underscores the need for a measure of LV function in all patients for accurate risk stratification prior to PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The fastest growing age group in the United State is the elderly . Elderly patients are particularly predisposed to developing calcified plaques, have worse baseline clinical risk factors including worse left ventricular function, and are turned down for surgical and percutaneous revascularization more frequently than younger patients . The 30‐day MACCE rate was 2.2% in elderly patients and was identical to the younger patients, even though the elderly group had nearly twice the number of patients who presented with MI.…”
Section: Discussionmentioning
confidence: 99%
“…The fastest growing age group in the United State is the elderly . Elderly patients are particularly predisposed to developing calcified plaques, have worse baseline clinical risk factors including worse left ventricular function, and are turned down for surgical and percutaneous revascularization more frequently than younger patients . The 30‐day MACCE rate was 2.2% in elderly patients and was identical to the younger patients, even though the elderly group had nearly twice the number of patients who presented with MI.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis suggested that depressed left ventricular function is an important independent predictor of worse 30-day mortality outcomes across all age groups [20]. Other large studies on consecutive patients undergoing PCI confirmed that predictors other than old age may have a greater influence on outcomes, and that risk stratification of PCI patients should take into account kidney injury, anemia, and low left ventricular function [17,18].…”
Section: Outcomes Of Percutaneous Coronary Intervention In the Elderlymentioning
confidence: 81%
“…This cohort differs from previous work, which has focused on the impact of LVEF in specific ACS syndromes 28 or in those who underwent revascularisation only. 5,29…”
Section: Discussionmentioning
confidence: 99%